A Coordination Analysis Of 20 kV Medium Voltage Distribution Protection System On LH 04 Gi Blang Pidie Feeder - Akhmad Nur Hidayat; Siti Anisah; Adi Sastra Pengalaman Tarigan (Jurnal Scientia, 2024)
In the electrical energy distribution system, power distribution systems, especially in the SUTM network, SKTM, and 20 kV distribution substations, can experience various obstacles that stop the distribution of electrical energy to consumers. In addition, various disturbances also cause damage to electrical equipment. One way to minimize or minimize the outage area and damage to various components that are electrified due to interference, a protection system is needed. More specifically, in avoiding the duration (SAIDI) and frequency (SAIFI) of customer outages, it is necessary to set the protection relay properly as a form of protection or protection so as to minimize the position and place of interference. Coordination of the protection system pattern of a network is said to be good if it can minimize the number of outages as small as possible based on the distance and location of the disturbance. After calculating the protection coordination system with ETAP simulation. In the ETAP simulation, the sequence of protection coordination has run well and the protection works in the correct order according to the calculation settings that have been input. The advantage of good protection system coordination is that if there is a disturbance at one point of the distribution network, it does not interfere with the production process in other distribution networks so that the number of outages can be reduced and the affected area can be localized as small as possible. The results of the coordination of the installed protection system on the distribution network utilizing ETAP can be seen that the existing OCR and GFR settings are still not good, for example, if there is a disturbance in the LH 04 feeder network, the relay sequence that releases the contact is LH 03, causing many customers to go out that should not be included. resetting OCR and GFR protection on the distribution network can be based on the fault current that occurs along the network. Overcurrent disturbances are used for low setting and high setting on OCR and GFR protection, for curve characteristics using inverse time standards combined with instantaneous relays. By resetting the OCR and GFR on the distribution network, the reliability of the protection system coordination and the selectivity of the protection sequence are better than the existing conditions so as to create an ideal protection system coordination.